The preparation of lanthanide macrocyclic complexes for use as MRI and luminescence contrast agents - Sparke, Amanda E. (2008)
Multimodality imaging agents have the potential to be detected in both MRI and optical imaging experiments allowing for visualisation of biological systems from the cellular level up to the whole body. Lanthanide complexes have shown great promise as components of compounds that can act as either MRI contrast agents or luminescent imaging agents dependent on the metal centre incorporated (e.g. gadolinium(III) or europium(III)/terbium(III)respectively). This thesis describes the design, synthesis and characterisation of multimodality lanthanide imaging agents. The synthesis of a series of lanthanide chelators based on DO3A bearing a benzimidazole or a benzyl derivative that can act as both a chromophore unit and a linking group for conjugation that has the functionality to couple to an optical dye (either rhodamine or BODIPY derivatives) is discussed. A series of lanthanide complexes with either a nitro- or amino-benzyl benzimidazole DO3A chelator or with an aminobenzyl DO3A chelator have been prepared. A number of strategies have been attempted to couple the complexes to an optical dye to form a multimodality imaging agent. Physical properties and cellular uptake of the lanthanide complexes have been investigated. It was shown that the benzimidazole ligands can sensitise the luminescence of both the europium(III) and terbium(III) metal ions. Relaxation rates of the gadolinium(III) benzimidazole DOS A complexes are comparable to that of commercial contrast agents. The relaxivity of the gadolinium(III) complex formed with the ligand l,4,7-tris(carboxymethyl)-10-(l-(4-nitrobenzyl)-2-methyl benzimidazole)-1,4,7,10-tetraazacyclododecane (34) is 6.22 mM"1 s" 1 , with the relaxivity of the gadolinium(III) complex formed with 1,4,7-tris(carboxymethyl)-10-( 1 -(4-aminobenzyl)-2-methyl benzimidazole)-1,4,7,10-tetraazacyclododecane (37) was found to be lower at 4.51 mM"1 s" 1 . The luminescence lifetimes of the europium(III) and terbium(III) complexes in and D2O were used to calculate the number of coordinated water molecules in aqueous solution [q = 1.19 for the europium(III) complex of (34), 0.7-0.8 for the europium(III) complex of (37) and 1.25 for the terbium(III) complexes of (34)]
HydraID: hull:5736 Hydra Discover Access Group: public ETD Collection: ETDChemistry
Keywords: Chemistry